2014
DOI: 10.4028/www.scientific.net/amr.986-987.80
|View full text |Cite
|
Sign up to set email alerts
|

FEC-LiTFSI-Pyr<sub>1A</sub>TFSI Ionic Liquid Electrolyte to Improve Low Temperature Performance of Lithium-Ion Batteries

Abstract: N-methyl-N-allylpyrrolidinium bis (trifluoromethanesulfonyl) imide (PYR1ATFSI) with substantial supercooling behavior is synthesized to develop low temperature electrolyte for lithium-ion batteries. Additive fluoroethylene carbonate (FEC) in LiTFSI/PYR1ATFSI/EC/PC/EMC is found that it can reduce the freezing point. LiFePO4/Li coin cells with the FEC-PYR1ATFSI electrolyte exhibit good capacity retention, reversible cycling behavior at low temperatures. The good performance can be attributed to the decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Wang et al offered to use a 1% 1-ethyl-3-methylimidazolium tetrafluoroborate (EMI-BF 4 ) as an ionic liquid-type electrolyte additive to form stable SEI on LiNi 0.5-Co 0.2 Mn 0.3 O 2 (NCM523)/graphite batteries to improve the LT performance [150]. The authors state that by adding EMI-BF 4 , battery capacity retention increases by 11.5% after 150 cycles at − 10 • C, and the discharge capacity almost doubles at − 30 • C. Zhang et al synthesized new N-methyl-N-allylpyrrolidinium bis (trifluoromethanesulfonyl) imide (PYR1ATFSI) ionic liquid electrolyte to improve LT battery performance [172]. Studies of the effect of FEC in LiTFSI/PYR1ATFSI:EC: PC:EMC electrolyte on LiFePO 4 /Li coin cells have shown promising results at low temperatures down to − 60 • C due to a decrease in the freezing point and polarization of the composite electrolyte.…”
Section: Additivesmentioning
confidence: 99%
“…Wang et al offered to use a 1% 1-ethyl-3-methylimidazolium tetrafluoroborate (EMI-BF 4 ) as an ionic liquid-type electrolyte additive to form stable SEI on LiNi 0.5-Co 0.2 Mn 0.3 O 2 (NCM523)/graphite batteries to improve the LT performance [150]. The authors state that by adding EMI-BF 4 , battery capacity retention increases by 11.5% after 150 cycles at − 10 • C, and the discharge capacity almost doubles at − 30 • C. Zhang et al synthesized new N-methyl-N-allylpyrrolidinium bis (trifluoromethanesulfonyl) imide (PYR1ATFSI) ionic liquid electrolyte to improve LT battery performance [172]. Studies of the effect of FEC in LiTFSI/PYR1ATFSI:EC: PC:EMC electrolyte on LiFePO 4 /Li coin cells have shown promising results at low temperatures down to − 60 • C due to a decrease in the freezing point and polarization of the composite electrolyte.…”
Section: Additivesmentioning
confidence: 99%
“…In a wide temperature range, particularly at low temperatures, the batteries utilizing the electrolyte with the enhanced formulation signify the lower charge-transfer resistance, higher Li + diffusion coefficient, and greater cyclic stability and rate performances. Furthermore, in recent years, several studies have been conducted and various breakthroughs have occurred in order to lift the capabilities of cells in cold conditions. For example, Ignatova et al suggested that the addition of 15-crown-5 to the electrolyte was to enhance the primary Li/CFx cell’s characteristics at low temperatures. On two electrolytes based on 1 M LiBF 4 in GBL and 1 M LiPF 6 in a mixture of EC/DMC/EMC (1:1:3), the beneficial effect of improving the discharge capacity at low temperatures (−50 °C) has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Among several components of LIBs, their electrolyte is very important because it has an evident effect on the redox reaction mechanism of cells. The standard electrolyte system 1 M LiPF 6 + ethylene carbonate (EC)/diethyl carbonate (DEC) is currently commercially available, but the most significant issue is that its application temperature range is extremely limited. At low temperatures the electrolyte experiences a number of issues, including increased viscosity, decreased conductivity, increased cathode–electrolyte interface (CEI) film impedance, and reduced lithium-ion migration rate, especially, finally making a fast decline and even breakdown of the LIB’s performance. Many studies have been undertaken with the goal of improving the battery’s low-temperature performance in recent years. For instance, Smart et al demonstrated excellent low-temperature performances by comparing methylbutyrate (MB) and ethyl butyrate (EB) electrolyte additives, and excellent low-temperature performances were obtained at −60 °C with C/20 . The discharge capacity retention at current density is more than 80% of that at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%